Linkage between financial inclusion and Indonesian welfare: a recent evidence - Paidi Hidayat; Raina Linda Sari (Cogent Business & Management, 2022)
This paper provides the linkage between financial inclusion and welfare in Indonesia. This paper analyzes the level of financial inclusion Indonesian welfare using provincial data during 2015-2018. Index of Financial Inclusion (IFI) is calculated based on the dimensions of accessibility, availability, and usage of financial services. We employ the generalized least square (GLS) method for panel data estimation. Evidence showed that financial inclusion in Indonesia which mostly determined by the dimensions of the use and availability of financial services, while the accessibility dimension was relatively low in Indonesia. Based on the financial inclusion index, 25 provinces were grouped in the low financial inclusion, 8 provinces in the medium category and only DKI Jakarta Province categorized as high financial inclusion. The panel data estimation results show that the financial inclusion index has a positive and significant effect on the welfare of the Indonesian people as proxied by the human development index. The level of financial inclusion remains uneven between province in Indonesia. The lowest level of financial inclusion related to accessibility. The government should provide socialization and education of financial products to the public community, especially formal financial services such as banks. Financial literacy played an important role to improve welfare as a whole.
Keywords: 650; Financial inclusion; financial literacy; generalized least square; welfare